Circulating Very Long‐Chain Saturated Fatty Acids and Heart Failure: The Cardiovascular Health Study. Issue 21 (6th November 2018) - Lemaitre, Rozenn N.; McKnight, Barbara; Sotoodehnia, Nona; Fretts, Amanda M.; Qureshi, Waqas T.; Song, Xiaoling; King, Irena B.; Sitlani, Colleen M.; Siscovick, David S.; Psaty, Bruce M.; Mozaffarian, Dariush
Abstract : Background: Circulating very‐long‐chain saturated fatty acids (VLSFAs) are integrated biomarkers of diet and metabolism that may point to new risk pathways and potential targets for heart failure (HF) prevention. The associations of VLSFA to HF in humans are not known. Methods and Results: Using a cohort study design, we studied the associations of serially measured plasma phospholipid VLSFA with incident HF in the Cardiovascular Health Study. We investigated the associations of time‐varying levels of the 3 major circulating VLSFAs, lignoceric acid (24:0), behenic acid (22:0), and arachidic acid (20:0), with the risk of incident HF using Cox regression. During 45030 person‐years among 4249 participants, we identified 1304 cases of incident HF, including 489 with preserved and 310 with reduced ejection fraction. Adjusting for major HF risk factors and other circulating fatty acids, higher levels of each VLSFAs were associated with lower risk of incident HF ( P trend≤0.0007 each). The hazard ratio comparing the highest quintile to the lowest quintile was 0.67 (95% confidence interval, 0.55–0.81) for 24:0, 0.72 (95% confidence interval, 0.60–0.87) for 22:0 and 0.72 (95% confidence interval, 0.59–0.88) for 20:0. The associations were similar in subgroups defined by sex, age, body mass index, coronary heart disease, and diabetes mellitus. Among those with ejection fraction data, the associations appeared similar for those with preserved and with reduced ejection fraction. Conclusions: Higher levels of circulating VLSFAs are associated with lower risk of incident HF in older adults. These novel associations should prompt further research on the role of VLSFA in HF, including relevant new risk pathways. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00005133.